2022
DOI: 10.1007/s00223-022-00970-4
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle Related Fluctuations in Circulating Markers of Bone Metabolism at Rest and in Response to Running in Eumenorrheic Females

Abstract: The aim of this study was to investigate potential fluctuations in bone metabolic markers across the menstrual cycle both at rest and after a 30-minute bout of vigorous-intensity running at 80% of 𝑉 ̇O₂max. Resting and post-exercise (0, 30, 90 min) sclerostin (inhibitor of bone formation), parathyroid hormone (PTH, regulator of calcium homeostasis), carboxy-terminal cross-linking telopeptide of type I collagen (β-CTX, marker of bone resorption), and procollagen type 1 N propeptide (P1NP, marker of bone format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 145 publications
3
5
2
Order By: Relevance
“…Bone formation, measured by P1NP concentrations, and bone resorption, determined by β- CTX-1, were affected by MC-related fluctuations following exercise, showing greater bone formation in the LFP and reduced bone resorption during the MLP. These results are not in line with those shown by Guzman et al 12 where no differences were shown between MC phases [mid-late follicular phase (day 8±1) and luteal phase (day 22±3)] in a group of seven eumenorrheic females. Nevertheless, it should be noted that the Guzman et al 12 study did not measure the EFP (in this study day 4±1) nor the LFP (as defined in the present study as 1-3 days before the ovulation day, day 12±2), but rather measured the mid or late follicular phase, depends on the individual characteristics of each female’s MC.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Bone formation, measured by P1NP concentrations, and bone resorption, determined by β- CTX-1, were affected by MC-related fluctuations following exercise, showing greater bone formation in the LFP and reduced bone resorption during the MLP. These results are not in line with those shown by Guzman et al 12 where no differences were shown between MC phases [mid-late follicular phase (day 8±1) and luteal phase (day 22±3)] in a group of seven eumenorrheic females. Nevertheless, it should be noted that the Guzman et al 12 study did not measure the EFP (in this study day 4±1) nor the LFP (as defined in the present study as 1-3 days before the ovulation day, day 12±2), but rather measured the mid or late follicular phase, depends on the individual characteristics of each female’s MC.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are not in line with those shown by Guzman et al 12 where no differences were shown between MC phases [mid-late follicular phase (day 8±1) and luteal phase (day 22±3)] in a group of seven eumenorrheic females. Nevertheless, it should be noted that the Guzman et al 12 study did not measure the EFP (in this study day 4±1) nor the LFP (as defined in the present study as 1-3 days before the ovulation day, day 12±2), but rather measured the mid or late follicular phase, depends on the individual characteristics of each female’s MC. Moreover, luteal phase testing was scheduled 1 week after a positive LH detection kit test (day 22±3) in the Guzman et al 12 trial, coinciding with our timing of MLP measurement (day 21±3).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Estrogen inhibits osteoclast activity to regulate bone resorption and can become chronically suppressed during longer‐term LEA 53,54 . Recent evidence suggests that hormonal fluctuations during the menstrual cycle do not cause predictable variations in bone marker concentrations, 55,56 but, nonetheless, all conditions in the current study were completed within the early follicular phase of the menstrual cycle to minimize estrogen fluctuations. 17β‐estradiol concentrations remained stable during all conditions, suggesting changes in β‐CTx (or P1NP) during 3 days of LEA are not greatly influenced by estrogen.…”
Section: Discussionmentioning
confidence: 95%